Studien zur chemischen Dynamik: nach J. H. van 't Hoff's Etudes de dynamique chimique; 49 figuren im text - Cohen E. Ernst; van't Hoff J. H. Jacobus Henricus (Amsterdam, Frederik Muller & Co, 1896)
В описании используется грамматика 19 века